STRATEGI PENINGKATAN KUALITAS BUMDES DENGAN TEKNOLOGI PENGOLAHAN BERAS ANALOG DARI UMBI-UMBIAN - Shobirin, Mochammad Syafiuddin; Puspaningrum, Yessita; Faizah, Mazidatul; sholeh, Muh ibnu; Kresnanto, Hadi Asih (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
This study aims to formulate strategies for improving the quality of Village-Owned Enterprises (BUMDes) through the application of analog rice processing technology from tubers as a step towards food diversification and local economic development. Villages possess abundant natural resources, especially various types of tubers such as cassava and porang, but their utilization remains limited. The lack of knowledge and skills in processing local food resources has been a barrier to increasing the added value of these products. Analog rice processing technology using tubers can be a solution to enhance food diversification and create healthy and nutritionally valuable alternative products. The method used in this study includes field surveys to identify local potential, training and technical assistance in analog rice processing for BUMDes managers, and evaluation of the impact of the technology's implementation. The results show that the application of this technology successfully improved the quality and variety of products produced by BUMDes, while also opening new market opportunities for local analog rice products. Moreover, the program succeeded in enhancing the skills and knowledge of the community, particularly in managing local resources sustainably. This strategy is expected to serve as a model for other BUMDes to optimize local potential and improve the welfare of rural communities.